Fault-tolerant communication system based on convolutional code for the control of manipulator robots. (August 2020) - Urrea, Claudio; Kern, John; López, Ricardo
Abstract: This paper presents the development of a convolutional code application for error detection and correction in a communication system. This application is based on an industrial protocol and aims at reconstructing data damaged during transmission. The Controller Area Network (CAN) protocol is used, which is widely used in the automobile industry, as well as in the automation of industrial processes. The application allows us to make a system that presents errors due to hostile conditions in the fault-tolerant industrial environment. These errors appear as corrupted data affecting the robot's control system. The robot is a 3 Degrees of Freedom (3-DoF) manipulator robot with redundancy in the plane; data transmission takes place between the controller and such a robot. The communication system is assessed in terms of performance when facing transmission faults, comparing the response of the system with and without error correction. Highlights: Development of a convolutional code application for error detection and correction in a communication system. Redundant and coded data adds fault tolerance to CAN bus communication. Fault-tolerant communication used in a control loop improves performance. The experimental results show that corrupted data is corrected allowing the optimal operation of the robot. The scheme implemented can be applied to several automotive devices, including sensors and actuators.